Feeling and thinking: An affect‐as‐cognitive‐feedback account. Issue 5 (May 2017) - Ray, Cara; Huntsinger, Jeffrey R.
Abstract: Despite the abundance of evidence demonstrating a dedicated link between positive and negative affect and specific ways of thinking, not all findings are consistent with this view. New research suggests that the relationship between affect and thinking can be altered and often reversed, by varying the mental context in which affect is experienced. The affect‐as‐cognitive‐feedback account can explain a wide range of phenomena, including both prior findings and this more recent research, and generate new predictions. According to this account, affective reactions confer value on accessible information processing strategies (e.g., global vs. local processing) and other mental content that happens to be accessible at the time. This view underscores that the relationship between affect and cognition is not fixed but instead is highly malleable. We present evidence that supports this account, along with new findings that suggest a malleable influence of specific affective states on cognition.